Para-allopatry in hybridizing fire-bellied toads (Bombina bombina and B. variegata): Inference from transcriptome-wide coalescence analyses - Nürnberger, Beate; Lohse, Konrad; Fijarczyk, Anna; Szymura, Jacek M; Blaxter, Mark L (Evolution, 2016)
Ancient origins, profound ecological divergence, and extensive hybridization make the fire-bellied toads Bombina bombina and B. variegata (Anura: Bombinatoridae) an intriguing test case of ecological speciation. Previous modeling has proposed that the narrow Bombina hybrid zones represent strong barriers to neutral introgression. We test this prediction by inferring the rate of gene exchange between pure populations on either side of the intensively studied Kraków transect. We developed a method to extract high confidence sets of orthologous genes from de novo transcriptome assemblies, fitted a range of divergence models to these data and assessed their relative support with analytic likelihood calculations. There was clear evidence for postdivergence gene flow, but, as expected, no perceptible signal of recent introgression via the nearby hybrid zone. The analysis of two additional Bombina taxa (B. v. scabra and B. orientalis) validated our parameter estimates against a larger set of prior expectations. Despite substantial cumulative introgression over millions of years, adaptive divergence of the hybridizing taxa is essentially unaffected by their lack of reproductive isolation. Extended distribution ranges also buffer them against small-scale environmental perturbations that have been shown to reverse the speciation process in other, more recent ecotypes.
Keywords: hybridizace genetická; Hybridization, Genetic; tok genů; Animals; žáby; Phylogeny; transkriptom; Gene Flow; zvířata; Transcriptome; fylogeneze; rozšíření zvířat; Animal Distribution; Anura